2014
DOI: 10.1063/1.4886433
|View full text |Cite
|
Sign up to set email alerts
|

A Kirkpatrick-Baez microscope for the National Ignition Facility

Abstract: Current pinhole x ray imaging at the National Ignition Facility (NIF) is limited in resolution and signal throughput to the detector for Inertial Confinement Fusion applications, due to the viable range of pinhole sizes (10-25 μm) that can be deployed. A higher resolution and throughput diagnostic is in development using a Kirkpatrick-Baez microscope system (KBM). The system will achieve <9 μm resolution over a 300 μm field of view with a multilayer coating operating at 10.2 keV. Presented here are the first i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…We did not combine any spectral selection optics with our FZPs, meaning that the whole spectrum of our target is collected by our detector, resulting in a contrast and resolution loss giving us an upper limit for each FUHRIx2 channel. In a previous paper, 2 we showed that FZPs need their distances to be adjusted to the object position to match their calculated focal distance for a photon energy of 1630 eV (Al He α ). Considering the relation between the focal distance ( f λ ) and the wavelength (λ), where r 1 is the first zone radius, the distances are then calculated with the thin lens formula: 1/f λ = 1/p + 1/q, with p being the object-FZP distance and q being the FZP-detector distance.…”
Section: B Metrology On Equinoxmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not combine any spectral selection optics with our FZPs, meaning that the whole spectrum of our target is collected by our detector, resulting in a contrast and resolution loss giving us an upper limit for each FUHRIx2 channel. In a previous paper, 2 we showed that FZPs need their distances to be adjusted to the object position to match their calculated focal distance for a photon energy of 1630 eV (Al He α ). Considering the relation between the focal distance ( f λ ) and the wavelength (λ), where r 1 is the first zone radius, the distances are then calculated with the thin lens formula: 1/f λ = 1/p + 1/q, with p being the object-FZP distance and q being the FZP-detector distance.…”
Section: B Metrology On Equinoxmentioning
confidence: 99%
“…1 Over the last few years, the "Commissariatà l'énergie atomique et auxénergies alternatives" (CEA) has been investigating Fresnel zone plates (FZPs) as imaging optics to be used on a high-resolution imaging microscope for the Laser MegaJoule (LMJ) in the context of Inertial Confinement Fusion (ICF). Other solutions such as Kirkpatrick-Baez 2 or Wolter-type 3 microscopes have been preferred so far.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, KB microscopes have been limited to just four images with larger image separation (52 mm) and corresponding longer time separations (+350 ps) when two images are coupled to a single-strip framing camera. 8 Pickworth et al 9 have recently developed a KB mirror assembly for use at the National Ignition Facility 10 capable of being coupled to a four-strip, high-speed framing camera. Additionally, Yi et al 11 have implemented an eight-image KB mirror assembly also coupled to a four-strip framing camera.…”
Section: Introductionmentioning
confidence: 99%
“…Current 12 µm pinholes limit the observable modes at PV to those less than ∼120. An ideal candidate to improve the measurements is the Kirkpatrick-Baez Microscope [69], recently demonstrated on the NIF [70,71] that combines <8 µm resolution imaging with narrow band energy responsiveness in addition to a larger photon collection efficiency when compared to similar resolution imaging systems. This diagnostic will improve the measurements discussed here, allowing higher modes and lower amplitudes to be measured.…”
Section: Pacs Numbers: Valid Pacs Appear Herementioning
confidence: 99%